Physical and mental health anxiety : comparison of medical students and psychology students - Sigríður Kr. Kristjánsdóttir 1999- (2021)
Physical health anxiety among the public has been extensively investigated abroad over the past decades. Physical health anxiety among medical students has also been well documented, where some suggest that with increased medical knowledge, students present more symptoms of physical health anxiety. However, literature on anxiety regarding one’s mental health is limited. The current study aimed to examine the prevalence of physical health anxiety and mental health anxiety among medical and psychology students in Iceland. A self-administered questionnaire comprising demographic information, the Short Health Anxiety Inventory, the Mental Health Anxiety Inventory, and questions regarding social support, and Covid-19 anxiety were distributed to undergraduate students in psychology and medicine at the University of Iceland. A total of 117 responses were analyzed, from 59 medical students and 58 psychology students. The results from a two-way ANCOVA indicated that neither academic major nor gender had an effect on symptoms of physical health anxiety or mental health anxiety. The covariates, medical visits and parental social support, had a positive effect on physical health anxiety, whereas COVID-19 anxiety had a positive effect on mental health anxiety. Longitudinal studies on physical and mental health anxiety among university students are suggested for future research. Keywords: Physical health anxiety, mental health anxiety, psychology students, medical students Líkamlegur heilsukvíði meðal almennings hefur verið ítarlega rannsakaður erlendis síðastliðna áratugi. Þar að auki hefur mikið verið fjallað um líkamlegan heilsukvíða meðal læknanema þar sem sumir leggja til að með aukinni læknisfræðilegri þekkingu sýni nemar fleiri einkenni líkamlegs heilsukvíða. Aftur á móti hefur heilsukvíði er varðar andlega heilsu lítið verið rannsakaður. Markmið rannsóknarinnar var að kanna algengi líkamlegs heilsukvíða og andlegs heilsukvíða meðal læknanema og sálfræðinema á Íslandi. Spurningalista sem innihélt bakgrunnsbreytur, ...